Mobilising Public Opinion against Global Poverty - Fransman, Jude (OECD Development Centre Policy Insights, 2004)
Citizens in OECD countries quite unambiguously support more solidarity and justice at the international level; however, despite the adoption of the Millennium Development Goals (MDGs) by their governments in 2000, they remain insufficiently informed and educated about global development challenges. With increased understanding of the issues, citizens could provide greater support for more efficient and coherent development policies as well as for more funding. This requires new efforts by national authorities to report on desirable outcomes and on the results and effectiveness of international development policies towards achieving them